Effect of Sugar Concentration on Physical and Chemical Characteristics of Kombucha Seaweed (Gracilaria verrucosa) - Gustishio, Averio; Monica Sahidu, Adriana; saputra, eka (Journal of Marine and Coastal Science, 2023)
Seaweed has been identified to increase endurance, anti-cancer, prevent premature aging, maintain skin smoothness. The potential for developing kombucha tea is very large in Indonesia, because until now there is no industry that produces and sells kombucha tea widely. Kombucha is an herbal product in the form of a drink which is the result of a symbiosis of bacteria and yeast containing a number of vitamins, minerals, enzymes, and organic acids. Kombucha tea is also beneficial for health, namely as an antioxidant, antibacterial, improving intestinal microflora, increasing body resistance and lowering blood pressure. The purpose of this study was to determine the effect of sugar concentration on the physical and chemical characteristics of Gracilaria verrucosa seaweed kombucha tea. The study was carried out using a one factorial completely randomized design. The treatment of sugar concentration was 9%, 10%, 11% and 12%. The results showed that with the addition of the higher sugar concentration, the higher the viscosity and alcohol content, while the pH value and vitamin C content were inversely proportional to the added sugar concentration.The optimal treatment was found at a sugar concentration of 9% because it had viscosity and pH values that were not much different from P0 as comparison data, and had the highest vitamin C content and the lowest alcohol content.